Analisis Conjoint pada Antarmuka Pelanggan dan Perancangan Elektronic Marketing Rumah Makan - Utari, Vani (Bina Nusantara University, 2014)
This research aims to analyze 3 of 7 Steps Internet marketing and to produce market penetration strategy by developing an e-marketing-based website that is expected to help in decision making. E-marketing is a marketing strategy that can be carried out by the company with the utilization of Internet. Aie Badarun is a business entity engaged in the restaurant business that provides various menus. This research used Porter’s industry analysis, framework of seven stages of Internet marketing, conjoint analysis, and Object-Oriented Analysis and Design (OOAD). The outcome of the analysis is known that a feasible strategy for the company is leveraging the Internet as marketing media. E-marketing strategy through Restaurant Aie Badarun website is expected to be able to give customers the information needed about the product or menu of food and drink, customer testimonials, online reservation, and finding solutions to their queries about products and services of Restaurant Aie Badarun using 7C Framework which is a combination of attributes and website design. E -marketing strategy could support the overall restaurant marketing.